Sustainable agriculture through rhizosphere bacteria for plant growth promotion, nutrient acquisition, and stress alleviation - Muhammad Qasim Hussain; Seerat Fatima; Aiman Nawaz; Sana Hafeez; Muhammad Waqar Alam; Salah ud Din; Talha Ali Chohan; Shaheera Asif Butt; Muhammad Ahsan Shahzad; Azka Azhar; Lingling Li; Muhammad Zahid Mumtaz (International Journal of Applied and Experimental Biology)
Rhizosphere bacteria are attracting a lot of interest in sustainable agriculture because of their capacity to stimulate plant growth, improve nutrient uptake, and reduce stress in plants. A review of recent discoveries in the field of using rhizosphere bacteria for these advantageous agricultural techniques is given in this article. Rhizosphere bacteria facilitate plant growth by solubilizing inaccessible elements like phosphorus, potassium, zinc, and manganese by producing a variety of enzymes and organic acids. Furthermore, these bacteria support plant nutrition by fixing atmospheric nitrogen, a necessary component for plant growth and development. Moreover, some rhizosphere bacterial strains can inhibit plant diseases, which lessen the need for artificial chemical pesticides. Rhizosphere bacteria have improved plant stress tolerance by producing stress-related substances, including phytohormones and osmoprotectants. These bacteria also give rise to systemic resistance in plants, successfully allowing them to survive various biotic and abiotic challenges. Concerning climate change and environmental variations, this rhizosphere bacteria-mediated stress reduction component holds a tremendous potential for sustainable agriculture. But for rhizosphere bacteria-based agricultural techniques to be successfully utilized, a thorough grasp of their variety, ecological relationships, and mode of action are necessary. Optimizing application techniques, formulating bioinoculants, and considering environmental aspects are crucial for consistent and dependable outcomes through rhizosphere bacteria.